Pembelaan Terpaksa (Noodweer) Bukan Sebagai Dasar Penghentian Penyidikan (RechtJiva, 2024)
Article 109 paragraph (2) of the Criminal Code Procedure that carries murky norms not specifying the scope of the definition of conduct not considered as a criminal offence as the ground for enquiry dismissal, which leads to legal uncertainty of the enforcement of necessary defence ceased during the enquiry. Departing from the above issue, this research aims to find out what the definition of conduct not considered a criminal offence as the ground for enquiry dismissal in Article 109 paragraph (2) of the Criminal Code Procedure and whether necessary defence (noodweer) is categorised in the definition of act not considered as a criminal offence as the ground for the dismissal of enquiry. This study employs a qualitative juridical analysis method, specifically through an in-depth interpretation of legal materials, as is typical in normative legal research. The legal materials were analysed based on descriptive analysis determining the definition of the rules specified in the Criminal Code, Criminal Code Procedure, and the notions of criminal experts. The research results reveal that conduct not considered a criminal offence involves acts within the scope of private law, administrative law, trade law, or adat law because the conduct concerned does not fit the aspects of criminal offences (particularly in terms of objective aspects). The necessary defence, therefore, cannot be dismissed in the process of enquiry simply because it violates the provisions of the Criminal Code Procedure, but it has to be proven before the court to guarantee that substantive material can be obtained according to the principle of proportionality and subsidiarity and to prevent subjective judgement and abuse of power.